THE GAME TECHNIQUE NTCHNIQUE STIMULATING LEARNING ACTIVITY OF JUNIOR STUDENTS SPECIALIZING IN ECONOMICS - Juri. S. Ezrokh (Russian State Vocational Pedagogical University, 2015)
The research is aimed at specifying and developing the modern control system of current academic achievements of junior university students; and the main task is to find the adequate ways for stimulating the junior students' learning activities, and estimating their individual achievements.Methods: The author applies his own assessment method for estimating and stimulating students' learning outcomes, based on the rating-point system of gradually obtained points building up a student's integrated learning outcomes.Results: The research findings prove that implementation of the given method can increase the motivational, multiplicative and controlling components of the learning process.Scientific novelty: The method in question is based on the new original game approach to controlling procedures and stimulation of learning motivation of the economic profile students.Practical significance: The recommended technique can intensify the incentivebased training activities both in and outside a classroom, developing thereby students' professional and personal qualities.